Taking on Diversity : How We Can Move from Anxiety to Respect. - Nacoste, Rupert (Prometheus Books, 2015)
In this enlightening book, a campus "diversity doctor" relates stories that individuals have shared with him about their anxieties in situations involving people who are in some way different than themselves. Dr. Rupert W. Nacoste regularly counsels students at North Carolina State University about their problems dealing with diversity of all kinds, including of gender, race, ethnicity, and sexual-orientation. Here, he shares his most effective techniques for handling the unavoidable realities of being in a neo-diverse community, whether that means in college or America as a nation. The author.